Belt and Road Environmental Implications for South Asia - Ali, Majid; Faqir, Khan; Haider, Bilal; Shahzad, Khurram; Nosheen, Nosheen (Frontiers in Public Health, 2022)
The Belt and Road Initiative (BRI) can play a significant role in the sustainable development of South Asia if appropriately implemented. Apart from the economic, trade, and cultural benefits of this colossal infrastructure, less is known about its environmental impact on South Asia. This study looks closely at the potential impact of the BRI on the South Asian environment. This research is based on the government-issued environmental policies, peer-reviewed literature, media articles, and reports. It has been suggested that the BRI could have a negative impact on the South Asian environment, which provided if does not consider the Paris agreement with its partners in the region. The study suggests that partner countries should adopt the BRI project to the principles of environmental impact assessment.